Transaksi Online dan Pembayaran Cash On Delivery (COD) Ditinjau dari Kitab Undang Undang Hukum Perdata - Ana Maria Marero Meka; Yossie M.Y. Jacob; Helsina Fransiska Pello (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
The development of information technology has driven changes in society’s transaction patterns, one of which is online transactions. Although electronic payment systems are increasingly common, the Cash on Delivery (COD) method remains popular due to its perceived safety and practicality. However, this method also raises legal issues, particularly concerning consumer protection and dispute resolution. This study aims to examine online transactions and COD payments based on the Indonesian Civil Code (KUH Perdata), as well as to analyze the dispute resolution procedures that may arise. The research method used is normative legal research with a statutory and conceptual approach. The results show that COD transactions constitute valid agreements if they meet the conditions outlined in Article 1320 of the Civil Code. However, in practice, cases of breach of contract and unlawful acts are still frequently found. Dispute resolution may be pursued through court litigation or alternative dispute resolution (ADR). In conclusion, legal protection for consumers in COD transactions needs to be strengthened through clearer and more specific regulations to ensure consumer rights remain protected.